2003
DOI: 10.1073/pnas.1331931100
|View full text |Cite
|
Sign up to set email alerts
|

From latent disseminated cells to overt metastasis: Genetic analysis of systemic breast cancer progression

Abstract: According to the present view, metastasis marks the end in a sequence of genomic changes underlying the progression of an epithelial cell to a lethal cancer. Here, we aimed to find out at what stage of tumor development transformed cells leave the primary tumor and whether a defined genotype corresponds to metastatic disease. To this end, we isolated single disseminated cancer cells from bone marrow of breast cancer patients and performed singlecell comparative genomic hybridization. We analyzed disseminated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
459
2
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(491 citation statements)
references
References 37 publications
19
459
2
11
Order By: Relevance
“…Our results and these published data on the stability of HER2 status between primary and metastatic tumours are in contrast with the recently published studies by Schmidt-Kittler et al (2003) and by Klein et al (Mercapide et al 2002) showing that micrometastatic cells demonstrated fewer chromosomal alterations, such as losses and gains detected by single-cell CHG analysis, than primary tumour cells (Mercapide et al 2002;Schmidt-Kittler et al, 2003). Another recently published study also showed that HER2 amplification was more frequently observed in circulating cells than in primary tumours and therefore concluded that HER2 amplification could be acquired during the metastatic process (Meng et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results and these published data on the stability of HER2 status between primary and metastatic tumours are in contrast with the recently published studies by Schmidt-Kittler et al (2003) and by Klein et al (Mercapide et al 2002) showing that micrometastatic cells demonstrated fewer chromosomal alterations, such as losses and gains detected by single-cell CHG analysis, than primary tumour cells (Mercapide et al 2002;Schmidt-Kittler et al, 2003). Another recently published study also showed that HER2 amplification was more frequently observed in circulating cells than in primary tumours and therefore concluded that HER2 amplification could be acquired during the metastatic process (Meng et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Correspondingly, Schmidt-Kittler et al (2003) have reported an early dissemination of single breast cancer cells with different chromosomal aberrations from the primary tumour to the surrounding healthy tissue. Absence of several alterations detected in the primary tumour suggested dissemination not only from the most advanced clone but also from pre-stages before immortalisation (Schmidt-Kittler et al, 2003). Alternatively, one might hypothesise that BTL3 is not derived from BTL1 but represents a second unrelated metachronous glioblastoma as has been reported before (Inda et al, 2003).…”
Section: Discussionmentioning
confidence: 79%
“…In all seven cases, both FIP200 alleles were inactivated with two primary breast cancers containing compound heterozygous deletions in both alleles and the other five showing loss of heterozygosity (LOH) of FIP200 [31]. Furthermore, LOH of FIP200 was also observed in several primary breast cancer samples in another study [50]. These genetic data thus provide evidence that FIP200 might function as a tumor suppressor gene.…”
Section: The Potential Role Of Fip200 In Cancer Developmentmentioning
confidence: 64%